New graptolite, chitinozoan and acritarch records from the Pascha-Incamayo area, Cordillera Oriental, Argentina - Toro, Blanca Azucena (2010)
A new fossil assemblage bearing graptolites, chitinozoans and acritarchs is analyzed based on material collected in the Pascha-Incamayo area, Salta Province, NWArgentina. The occurrence of Hunnegraptus copiosus (Lindholm, 1991), associated with specimens of the genus Tetragraptus (Salter, 1863), is highly relevant to improve the age assignment and correlate the fossil-bearing levels previously assigned to the Devendeus Formation. Different stages in the development of the index species of the Upper Tremadocian H. copiosus Biozone are described and illustrated. The precise stratigraphic ranges of the associated chitinozoans and acritarchs are discussed, according to the biostratigraphic analysis, and the stratigraphic relationships for the studied section are considered.